1993
DOI: 10.1002/elan.1140050808
|View full text |Cite
|
Sign up to set email alerts
|

Postchromatographic electrochemical detection of carbohydrates at a silver oxide electrode

Abstract: Silver electrodes, when conditioned at sufficiently positive potentials in the presence of a strong base, can be made to form a silver(1) oxide or silver(I1) oxide surface. In the presence of this oxide surface, carbohydrates may be oxidized and quantitated by means of an electrocatalytic scheme. The current which flows to reoxidize the charge-transfer mediator (silver oxide) is directly related to concentration of carbohydrate. Rectilinear response is obtained over at least IXO decades of concentration M to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Besides these features, Ag/Ag 2 O-f-MWCNTs show a prominent shoulder marked as C / 1 which is found to be complimentary with A / 1 and attributed to the reduction of AgOH back to silver. In case of Ag disk electrode, the intensity of peak A 1 is similar as in the absence of glucose since there is no native silver oxide present on the surface of electrode compared to Ag/Ag 2 O-f-MWCNTs electrode while that of A 2 peak shows a negligible decrease [30] since the outer surface layer of AgO available on the electrode for glucose oxidation is less and the inner layer transformation of Ag 2 O to AgO is perhaps not much affected in the presence of glucose due to geometrical hindrance of the surface layer. Further, Ag 2 O formed through glucose oxidation (A 2 ) would get re-oxidized to AgO at A 3 so the current at peak attributed to outer surface of oxide layer show increase in A 3 (refer Fig.…”
Section: Cyclic Voltammetrymentioning
confidence: 74%
See 1 more Smart Citation
“…Besides these features, Ag/Ag 2 O-f-MWCNTs show a prominent shoulder marked as C / 1 which is found to be complimentary with A / 1 and attributed to the reduction of AgOH back to silver. In case of Ag disk electrode, the intensity of peak A 1 is similar as in the absence of glucose since there is no native silver oxide present on the surface of electrode compared to Ag/Ag 2 O-f-MWCNTs electrode while that of A 2 peak shows a negligible decrease [30] since the outer surface layer of AgO available on the electrode for glucose oxidation is less and the inner layer transformation of Ag 2 O to AgO is perhaps not much affected in the presence of glucose due to geometrical hindrance of the surface layer. Further, Ag 2 O formed through glucose oxidation (A 2 ) would get re-oxidized to AgO at A 3 so the current at peak attributed to outer surface of oxide layer show increase in A 3 (refer Fig.…”
Section: Cyclic Voltammetrymentioning
confidence: 74%
“…Interaction of MWCNTs with silver demonstrate synergistic role in electrochemical redox behavior of silver in alkali solution which is found to be advantageous in glucose oxidation. Choice of silver is due to formation of both, Ag 2 O and AgO at sufficiently positive potentials [30,31]. AgO so formed at þ 0.75 V being unstable facilitates oxidation of glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum [14], silver [16], gold [17], copper [18], nickel [19], iron and cobalt [20] have been commonly used (tested) as electro-catalytic materials for GOR. The experimental results showed that glucose electrooxidation strongly depends on the electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work we found that carbonate ion can be incorporated into the oxide layer [15]. This article details studies directed towards the optimization of factors such as oxide layer thickness, ratio of silver(II) to silver(I) and mechanical stability of the oxide layer.…”
Section: Introductionmentioning
confidence: 98%
“…The chemistry of silver has been extensively studied and discussed in this article. Previous studies have indicated that the substrate reacts chemically with silver(II) oxide on the surface of the electrode, which is then re-oxidized at a potential of þ450 mV (vs. SCE) [15,16]. It is important to note that as one scans in the positive direction, the oxidation of the silver(II) is halted at more positive potentials.…”
Section: Introductionmentioning
confidence: 99%